RNA interactomics: recent advances and remaining challenges [version 1; referees: 2 approved] - Brigitte Schönberger (F1000Research, 2018)
Tight regulation of cellular processes is key to the development of complex organisms but also vital for simpler ones. During evolution, different regulatory systems have emerged, among them RNA-based regulation that is carried out mainly by intramolecular and intermolecular RNA–RNA interactions. However, methods for the transcriptome-wide detection of these interactions were long unavailable. Recently, three publications described high-throughput methods to directly detect RNA duplexes in living cells. This promises to enable in-depth studies of RNA-based regulation and will narrow the gaps in our understanding of RNA structure and function. In this review, we highlight the benefits of these methods and their commonalities and differences and, in particular, point to methodological shortcomings that hamper their wider application. We conclude by presenting ideas for how to overcome these problems and commenting on the prospects we see in this area of research.